The Importance of Money Scale (IMS): A new instrument to measure the importance of material well-being. (January 2022) - Franzen, Axel; Mader, Sebastian
Abstract: A fundamental assumption in the social sciences is that humans are motivated by the concern for material well-being. However, despite its central importance for many behavioral areas (e.g. consumption, labor market decisions, participation in education), there is no satisfying survey instrument to measure the importance of material well-being. In this paper, we suggest a short 8-item scale to measure the importance of money. In study 1, we test the new scale in a sample of 510 students with respect to its reliability, construct validity, and external validity using the multitrait-multimethod approach first suggested by Campbell and Fiske (1959). In study 2, we test the scale in a random population sample ( N  = 2914) with respect to its external validity. Our results suggest that the new importance of money scale (IMS) has high reliability and validity, and outperforms comparable measures with respect to its external and predictive validity. Highlights: Suggesting a new scale to measure the importance of material-well being. Validating the scale by using the multitrait-multimethod approach. The new scale has higher reliability and higher validity than comparative instruments.